Research on the Current Status of Joint Brand Marketing in Tourism Activities: A Factor Detection Analysis Based on 10 Prefecture-Level Cities in Shaanxi Province - Ren, Yuhang; Li, Dong; Chen, Juntong (International Journal of Global Economics and Management, 2025)
This study focuses on 10 prefecture-level cities in Shaanxi Province, exploring the impact of joint tourism brand marketing on regional tourism competitiveness. Through entropy method, coupling coordination degree model, and geographic detector analysis, it was found that the cultural and tourism industry in Shaanxi exhibits significant gradient disparities. [1] Xi'an leads in coupling coordination, serving as the core engine for joint branding, while some cities exhibit weak cultural-tourism linkages. Cultural tourism factors have the greatest impact on tourism competitiveness, followed by consumption demand and capital investment, with multi-factor synergies showing significant "dual-factor enhancement" effects. Joint brand marketing effectively empowers regional tourism competitiveness through complementary resource chains but faces challenges such as limited radiation radius and "pseudo-joint" practices. The study proposes strategies like constructing a gradient-based collaborative brand system, breaking administrative barriers, and digital empowerment to provide references for high-quality development of Shaanxi's cultural and tourism industry.